Application of the Health Belief Model for Assessing Risk Behavior among Patients Experiencing Musculoskeletal Pain Treated with Acupuncture in Surakarta - Aditya, Stefanus; Murti, Bhisma; Demartoto, Argyo (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Musculoskeletal pain is a complaint that occurs in parts of the skeletal muscles which is felt by a person ranging from mild complaints to very painful. This study aimed to analyze the effects of perceived vulnerability, perceived benefits, perceived barriers, and self-efficacy on risky behavior in patients complaining of musculoskeletal pain treated with acupuncture. Subjects and Method: This was a cross-sectional study conducted in Surakarta, from November-December 2023. A total of 200 patients were selected using fixed disease sampling. The dependent variable was risk behavior for musculoskeletal pain. The independent variables were perceived vulnerability, perceived vulnerability, perceived benefits, perceived barriers, cues to action, and self-efficacy. The data were analyzed using a multiple linear regression. Results: Musculoskeletal pain risk behaviors (MSDs) decreased with increasing perceived susceptibility (b= -0.22; 95% CI= -0.29 to -0.16; p<0.001), perceived benefit (b= -0.09; 95% CI= -0.13 to -0.05; p<0.001), and self-efficacy (b= -0.06; 95% CI= -0.11 to -0.01; p=0.015) and increased with increasing perceived barriers (b= 0.05; 95% CI= 0.02 to 0.09; p= 0.002). Conclusion: Perceived vulnerability, perceived benefits, and self-efficacy decrease risk behavior in musculoskeletal pain patients, and perceived barriers increase risk behavior in musculoskeletal patients.